A Pictogram of Nipah Virus Infection and Treatment - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Nipah virus (NIV) belongs to Henipavirus genus in the family of paramaxoviridae, which are negative sense single stranded RNA virus.1 Nipah virus is naturally har- boured in fruit eating pteropid bats and is reported to cause neurological and respi- ratory disease in pigs, horses and humans. NIV infection is prevalent in the south Asian region. NIV infection is associated with high fatality rate, which is reported to be 40-75%. Below is a pictogram (Figure 1) of NIV infection, symptoms, pathology and currently known treatment options,2-4 which will be useful to patients as well as healthcare professionals.